Effect of different tillage practices and nitrogen level on wheat production under inner terai of Nepal - Bartaula, Sampurna; Panthi, Urbasi; Adhikari, Anil; Mahato, Mohan; Joshi, Darbin; Aryal, Krishna (Journal of Agriculture and Natural Resources, 2020)
A field experiment was conducted to evaluate the plant height, yield and yield attributes of wheat under different tillage practices and nitrogen level at Dang, Nepal during winter season 2018-19. The experiment was laid out in split plot design with two tillage practices viz. zero tillage and conventional tillage as main plot factor and four level of N viz. 50 kg ha-1, 75 kg ha-1, 100 kg ha-1and 125 kg ha-1 as sub plot factor and each replicated thrice. The result revealed that there is no significant relation between tillage practice and plant height of wheat while N level significantly affect the plant height. 125 kg N ha-1 recorded the highest plant height (110.7 cm). Zero tillage recorded the highest effective tiller m-2 (254) and grain yield (3.3 t ha-1) whereas spike length, grain spike-1, biological yield and harvest index were not significant with tillage practices. Regarding the N level, 125 kg N ha-1 recorded the highest effective spike m-2 (279), spike length (10.6 cm), grain spike-1 (48), thousand grain weight (46.3 g), grain yield (3.6 t ha-1) and biological yield (9.4 t ha-1). 50 kg N ha-1 recorded the highest harvest index (42.9%). The interaction between the tillage practice and nitrogen level showed the significant effect on grain yield and harvest index where as other parameters showed non-significant relation. The zero tillage with 125 kg N ha-1 recorded the highest grain yield (3.9 t ha-1).